A systematic review of best practices in HIV care. Issue 1 (2nd January 2016) - Maina, Geoffrey; Mill, Judy; Chaw-Kant, Jean; Caine, Vera
ABSTRACT: Best practices in HIV care have the potential to improve patient outcomes and inform practice. We conducted a systematic review of best practices in HIV care that were published from 2003 to 2013. Practices that demonstrated success in achieving desired results based on their objectives were included in the review. Two themes emerged from the eight articles reviewed: (a) the importance of linking newly diagnosed people living with HIV to care and (b) the role of integrated and comprehensive service provision in improving patient outcomes. Inconsistencies in reporting and arbitrary use of the term "best practices" were hurdles in this review.